Food antigen consumption and disease activity affect food‐specific IgG4 levels in patients with eosinophilic esophagitis (EoE). Issue 3 (31st August 2022) - McGowan, Emily C.; Medernach, Jonathan; Keshavarz, Behnam; Workman, Lisa J.; Li, Rung‐chi; Barnes, Barrett H.; Sauer, Bryan; Wilson, Jeffrey M.; Platts‐Mills, Thomas A. E.
Abstract: Introduction: High levels of serum food‐specific IgG4 (sIgG4) have been reported in patients with EoE. The objective of this study was to examine whether serum sIgG4 levels to foods and aeroallergens are higher in EoE patients than allergic controls and to investigate the association between sIgG4 and EoE clinical characteristics. Methods: This was a case–control study nested in a prospective EoE Cohort. EoE cases were defined per consensus guidelines, and controls were individuals with symptoms who were confirmed to be EoE‐negative on upper endoscopy. Demographic and clinical information was prospectively collected. Serum IgE and sIgG4 were measured to foods and aeroallergens by ImmunoCAP. Mean levels of sIgG4 were compared between cases and controls, and logistic regression models were used to examine predictors of elevated milk sIgG4 levels. Results: The analysis included 123 individuals (EoE n = 93, control n = 30) with a similar distribution of allergic disease between EoE patients and controls (86% vs. 93%; p = .30). EoE patients had significantly higher sIgG4 levels to all allergens evaluated, with the exception of birch ( p = .24). Milk sIgG4 levels were independently associated with milk consumption (OR 4.95; p = .01) and the presence of sIgE to milk (OR 4.23; p = .008). Conclusion: Serum sIgG4 levels to food and aeroallergen proteins were higher in patients with EoE than non‐EoE controls, and higher levels of milk sIgG4 were independently associated with milk consumption and the presence of sIgE to milk proteins. Whether sIgG4 plays a pathogenic role in EoE or could be used as an EoE biomarker remains unknown and warrants further study.